HLA class II allele DRB1*16:02 is associated with anti-NMDAR encephalitis. Issue 6 (13th January 2019) - Shu, Yaqing; Qiu, Wei; Zheng, Junfeng; Sun, Xiaobo; Yin, Junping; Yang, Xiaoli; Yue, Xiaoyang; Chen, Chen; Deng, Zhihui; Li, Shasha; Yang, Yu; Peng, Fuhua; et al.
Abstract : Background and objective: Aetiology and pathogenesis of anti- N -methyl-D-aspartate receptor (anti-NMDAR) encephalitis, the most common autoimmune encephalitis, is largely unknown. Since an association of the disease with the human leucocyte antigen (HLA) has not been shown so far, we here investigated whether anti-NMDAR encephalitis is associated with the HLA locus. Methods: HLA loci of 61 patients with anti-NMDAR encephalitis and 571 healthy controls from the Chinese Han population were genotyped and analysed for this study. Results: Our results show that the DRB1*16:02 allele is associated with anti-NMDAR encephalitis (OR 3.416, 95% CI 1.817 to 6.174, p=8.9×10 −5, padj =0.021), with a higher allele frequency in patients (14.75%) than in controls (4.82%). This association was found to be independent of tumour formation. Besides disease susceptibility, DRB1*16:02 is also related to the clinical outcome of patients during treatment, where patients with DRB1*16:02 showed a lower therapeutic response to the treatment than patients with other HLA alleles (p=0.033). Bioinformatic analysis using HLA peptide-binding prediction algorithms and computational docking suggested a close relationship between the NR1 subunit of NMDAR and the DRB1*16:02 . Conclusions: This study for the first time demonstrates an association between specific HLA class II alleles and anti-NMDAR encephalitis, providing novel insights into the pathomechanism of the disease.